Association between the Pro12Ala polymorphism of the peroxisome proliferator-activated receptor gamma gene and strength athlete status - Maciejewska-Karlowska, A.; Sawczuk, M.; Cieszczyk, P.; Zarebska, A.; Sawczyn, S. (PLOS ONE, 2013)
The 12Ala allele of the Peroxisome Proliferator-Activated Receptor gamma gene (PPARG) Pro12Ala polymorphism produces a decreased binding affinity of the PPARGamma2 protein, resulting in low activation of the target genes. The 12Ala allele carriers display a significantly improved insulin sensitivity that may result in better glucose utilisation in working skeletal muscles. We hypothesise that the PPARG 12Ala allele could be associated with strength athlete status in Polish athletes.